Are Stones Living? - Breda, Nadia (Lagoonscapes, 2022)
The article addresses a new theme in anthropology, focusing on intra-actions among humans and the mineral world. Within an anthropology of the environment, in the context of the Italian Piave river, where water and stones were described by old gatherers as living beings, my ethnography discerns a European form of animism that attributed subjectivity, intentionality, ability and agency to non-humans, revealing an interspecies network of relationships hidden by the western naturalistic worldview. These data contribute to a reflection on Descolian ontological animism, recomposing the discrepancies of perspectives vised as contrasting, as the Ingoldian perception of the living being, De Castro’s perspectivism, and Barad’s new materialism, towards an anthropology of life.